Frequency of Acute Kidney Injury in Patients Admitted to the Medical Intensive Care Unit at KRL Hospital, Islamabad - Akram, Hifsa; Nabi, Zahid; Butt, Hajra Arshad; Afaq, Iqra; Rahim, Hina; Rashid, Humayun (Indus Journal of Bioscience Research, 2025)
Objectives: To determine the frequency of acute kidney injury in patients admitted to the Medical Intensive Care Unit at a tertiary care hospital. Study design: Cross-sectional observational study. Place and duration of study: Department of Nephrology, KRL Hospital, Islamabad, from February 2025 to June 2025. Methodology: A total of 170 patients aged between 33 to 70 years admitted to the medical intensive care unit were enrolled in this study. Acute kidney injury was diagnosed using modified KDIGO criteria which was based on serum creatinine rise >0.3 mg/dL within 48 hours, >50% increase within 7 days, or urine output <0.5 mL/kg/hour for ≥6 consecutive hours. Data were further analyzed for classification of acute kidney injury and to find the associated factors in the development of this acute injury. Results: The mean age was 53.1 ± 9.98 years. Male patients were 57.6% of total study population while female patients were 42.4%. Acute kidney injury was diagnosed in 68 (40%) of cases. Among the diagnosed patients, 52.9% belonged to Stage I, 29.4% Stage II, and 17.6% Stage III of kidney injury. The increase in serum creatinine rise >0.3 mg/dL within 48 hours was the most common diagnostic criteria found in 42.6% of patients. Statistically significant associations were found between acute kidney injury and diabetes mellitus (47.1% vs 30.4%, p=0.03), hypertension (55.9% vs 36.3%, p=0.01), anemia (41.2% vs 21.6%, p=0.01), and prolonged MICU stay ≥5 days (33.8% vs 18.6%, p=0.02) while no significant associations were observed with dyslipidemia or obesity. Conclusion: Acute kidney injury occurs at a significant proportion of 2 out of 5 patients in the medical intensive care unit underscoring the importance of early identification of the incidence and to adopt strategies for improved patient outcomes.